Qur’anic Perspectives on Human Creation and Contemporary Reproductive Ethics: A Thematic and Interdisciplinary Study - Mohammad Akbar Abdullah; Ahmad Asfa Fakhrunnabil; Nur Aji Bagus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
The development of modern reproductive technologies such as In Vitro Fertilization (IVF), genetic engineering, and contraception presents ethical challenges that demand a normative response from the interpretation of the Qur’an. This research aims to analyze the verses of human creation through thematic interpretation and examine their relevance to modern reproductive issues within the framework of Islamic bioethics. The research uses a literature study approach with qualitative methods, sourced from classical and contemporary tafsir books, especially Tafsir Al-Misbah and Tafsir Al-Azhar, and supported by scientific literature in the fields of embryology and reproductive medicine. The results of the study show that QS. Al-Mu’minun verses 12-14 describe the successive stages of human creation that are in harmony with modern embryology. The map of the verses of human creation in the Qur’an includes the phases of nutfah, ‘alaqah, mudhghah, and the formation of bones and flesh scattered in various surahs. These findings confirm that IVF is acceptable as long as it does not violate the principle of nasab, genetic engineering is permissible for benefit-oriented therapeutic purposes, and contraception is seen as responsible reproductive planning. This study also found a paradigm shift in interpretation from textual-descriptive to contextual-reflective as the foundation of modern reproductive ethics.